An Empirical Analysis of the Capital Structure of Selected Quoted Companies in Nigeria (1990-2004) - Salawu, Rafiu Oyesola (2015)
This study carried out an empirical analysis of capital structure of selected quoted companies in Nigeria. Specifically, it examined the effects of the identified determinants of capital structure of quoted companies on leverage and also analysed the impact of capital structure on profitability of quoted companies in Nigeria. This was with a view to establishing the pattern of capital structure choice and the underlining factors influencing it.